Towards personalized agriculture: what chemical genomics can bring to plant biotechnology - Stokes, Michael E.; McCourt, Peter (Frontiers in Plant Science, 2014)
In contrast to the dominant drug paradigm in which compounds were developed to “fit all”, new models focused around personalized medicine are appearing where treatments are customized for individual patients. The agricultural biotechnology industry should also think about these new personalized models. For example, most common herbicides are generic in action, which led to the development of genetically modified crops to add specificity. The ease and accessibility of modern genomic analysis should facilitate the discovery of chemicals that are more selective in their utility. Is it possible to develop species-selective herbicides and growth regulators? More generally put, is plant research at a stage where chemicals can be developed that streamline plant development and growth to various environments? We believe the advent of chemical genomics now opens up these and other opportunities to personalize agriculture. Furthermore, chemical genomics does not necessarily require genetically tractable plant models, which in principle should allow quick translation to practical applications. For this to happen, however, will require collaboration between the Ag-biotech industry and academic labs for early-stage research and development.